Return to sender - Alvarez, Julia (Yearling, 2009)
After his family hires migrant Mexican workers to help save their Vermont farm from foreclosure, eleven-year-old Tyler befriends the oldest daughter, but when he discovers they may not be in the country legally, he realizes that real friendship knows no borders.